The city of death - Chadda, Sarwat (Chadda, Sarwat. Ash Mistry chronicles, 2013)
British schoolboy Ash Mistry, the reincarnation of the great Indian hero Ashoka and an agent of the goddess of death, faces the evil Lord Savage again after the villain sends his minions to capture Gemma, Ash's unrequited crush.